Democracy During the Old Order: A Study of Historical Characteristics - Arditya Prayogi; Riki Nasrullah; Bambang Kholiq Mutaqin (Yayasan Adra Karima Hubbi, 2024)
Background. Democracy is believed to be the best principle and system in a country's political and constitutional system. The treasures of thought and political performance in various countries have come to a common ground regarding this, namely that democracy is the best choice among various other options. Purpose. This study provide a historical description of the long history of democracy in Indonesia, especially during the Old Order era, both in the form of liberal democracy and guided democracy. Thus, this article can make a better contribution to understanding and interpreting the development of democracy in Indonesia. Method. The writing of this article uses a descriptive qualitative method with based on data mining through library research/literature studies from several literature sources. Results. It is clear that in the old order there were two types of democracy, namely liberal and guided democracy. In liberal democracy, people's freedom to participate in politics or political individualism is highly upheld. On the other hand, in a guided democracy, the people have political limitations because power is very centralized in the hands of a president. Conclusion. These forms of democracy must place the voice of the people, the interests of the people above all else so that in managing the country, attention to the people becomes the main thing.